2013
DOI: 10.1002/lary.24373
|View full text |Cite
|
Sign up to set email alerts
|

Management specificities of congenital laryngeal stenosis

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
0
22
0
2
Order By: Relevance
“…Six out of eight patients were managed successfully by EACS with ABD by Mirabile et al 39 seven patients. 41 Horn et al performed EACS with ABD for neonates with failure to extubate who would have been otherwise considered for an open anterior cricoid split. 40 They were able to successfully extubate two out of three patients.…”
Section: Discussionmentioning
confidence: 99%
“…Six out of eight patients were managed successfully by EACS with ABD by Mirabile et al 39 seven patients. 41 Horn et al performed EACS with ABD for neonates with failure to extubate who would have been otherwise considered for an open anterior cricoid split. 40 They were able to successfully extubate two out of three patients.…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopic techniques give comparable results to ACS. 19 As discussed earlier, ACS is beneficial only in low-grade SGS while its effect is not certain in high-grade stenosis. 4 In addition, presence of thickened anterior cricoid lamina in this case might make ACS difficult, especially with using cold instruments.…”
Section: Discussionmentioning
confidence: 96%
“…Worldwide use of high-pressure balloons have confirmed this to be an important tool in the treatment of SGS be it primarily or as an adjuvant method post airway reconstruction. Reported success rates for BL in the treatment of acquired SGS vary between 60% [15] and 100% [11,[16][17][18][19]. Recently Blanchard et al [18] have suggested that BL is a successful primary treatment for congenital SGS, in theory a poor indication for this since cartilage deformity is expected.…”
Section: Discussionmentioning
confidence: 97%